An industrial quality control study on New Universal Foods Corporation - Angeles, Wilfred Gabriel (College of Engineering, 2002)
This study presents a documentation and evaluation of the existing quality system of the New Universal Foods Corporation, a snack food manufacturer, using the tools provided in Statistical Quality Control. The New Universal Food Corporation is one of the many food companies here in the Philippines. Although it has its share of its customers with its growing product line, it has a relatively small amount of recognition in the snack foods business. New Universal Food Corporation is also one of the few production companies that do not completely automate its production process. It is semi-automated, with manual labor handling the labor-intensive procedures in the manufacturing process, i.e. putting give-away toys at one toy per pack. To determine the quality problems in the manufacturing of the Cheese Donut, which was one of the best selling products of NU Foods Corporation, the group utilized problem identification and analysis tools such as Pareto diagrams. The study also featured a Failure Mode and Effect Criticality Analysis, which was used to determine potential problems that might occur in the future. From these tools, the group was able to identify three problems namely, the varying fill weights, packaging misprints, and the incorrect product form being produced. These three quality problems then became the focus of the group's attention. The group then studied and identified the causes of these problems using Ishikawa diagram. With this tool the group found out that incorrect machine setting, machine error and miscalibration of the machine caused fill weight variation on packed products. For the incorrect product form, it was caused by incorrect cutting speed setting, wrong die used, varying speed setting, and non-uniform product mixture. And lastly, supplier inefficiency caused the packaging misprints. To study if the company's packaging process was in control, the group utilized control charts. The group used X and R charts for the varying fill weight, np-charts for the packaging misprints, and p-chart for the incorrect product form. With these charts the group was able to find out that the process of packaging was out of control, as well as the packaging materials supplied by the supplier. However, the process of product forming was found to be in control. With regards to their process capability, the packaging process had a process capability value of 1.208. This implies that the company has process potential that is below the recommended minimum value of 1.33. This means that the company has an unsatisfactory process. For its process capability index, it had a value of 1.1985. Cpk should be equal to Cp for the process to be centered; meaning that the actual process mean coincides with the specification. In this case, Cpk is less than the process capability potential, so it is off-centered. For the company's acceptance sampling, they employ 100 percent inspection on incoming raw materials and every raw material found to be unacceptable are returned and exchanged by the suppliers. For their finished product inspection, the company inspects 5 percent of one batch output. This is about 365 packs of Cheese Donuts. With a sample size of 365 they conduct a single sampling plan with 10 as their acceptance number. Through the company's records and through interviews with supervisors, the group has found out that their estimate percent defective is 2 percent. With these data, the group is able to compute for the probability of acceptance, which is 87.57 percent. If the lot batch is rejected the company perform rectification. With this they screen the rejected lot and replace all the defective items with acceptable one. All the defective items are then reworked, if possible, or downgraded. The group then suggested recommendations for each of the quality problem, keeping in mind that suggested recommendations must not be costly and must be easy to implement. For the problem of varying fill weight, the group recommended the posting of guidelines to remind workers to input the correct machine setting, while for the machine error and machine miscalibration, the group recommended the formulation of a preventive maintenance schedule to keep the packaging machines in good working condition. For the problem of incorrect product form, the group recommended the posting of guidelines to deal with the incorrect cutting speed setting and the usage of wrong die. To deal with varying cutting speed, the group recommended the purchase of voltage regulators and the formulation of preventive maintenance schedule. For the non-uniform product mixture, the group recommended to the company to review the mixing time of the mixers and to do necessary adjustments if mixing time varied from the specified mixing time. As for the problem of packaging misprints, the group's only recommendation was for the company to send one of its supervisor to the supplier's plant and to do the actual inspection there because it would be very difficult to inspect rolls of packaging if it had been rolled already.